Why permit telework? exploring the determinants of California City governments' decisions to permit telework - Kwon, Myungjung; Jeon, So Hee (2017)
This study examines what factors influence a local government$1 (Bs decision to permit its employees to telework. Drawing on insights from contingency theory, this study investigates how external forces influence California local governments$1 (Bdecisions regarding whether or not to permit telework for their employees. To examine this question, this article uses the 2010 International City/County Management Association survey data and the 2009 American Communities Survey by the U.S. Census Bureau as its primary data sources. The findings show that various contextual factors such as municipal climate protection efforts, citizen participation, population diversity, political institutions, and support from state legislators play a significant role in a city government$1 (Bs decision to permit telework for city employees.s
Keywords: Telecommuting; Government; California